Detecting and preventing collusion attack in DPoS based on power index - Xiaodong FU; Xinxin QI; Li LIU; Wei PENG; Jiaman DING; Fei DAI (Tongxin xuebao)
Since malicious nodes may manipulate voting elections through collusion attacks in consensus mechanism of DPoS, the security of block chain can not be guaranteed in the consensus process of DPoS.To deal with the problem, a method for detecting and preventing collusion attack in DPoS based on power index was proposed.Firstly, a weighted voting game model of DPoS was constructed based on the idea of power index in game theory, and the behavioral motivation of the malicious node could be analyzed.Then, the attacks were detected based on changing range of abnormal power index.During the process of preventing collusion attacks in DPoS, the Softsign activation function was adapted to suppress the power index of malicious nodes.Lastly, the effectiveness of the proposed method to detect and prevent collusion attacks in DPoS was verified through theoretical analysis and experiments.